Mechanics over micro and nano scales - Chakraborty, Suman 1973- (Springer, 2011)
em>Mechanics Over Micro and Nano Scales covers the recent developments in the fields of mechanics in all forms over micro, meso and nano scales. Special emphasis is given to fundamental aspects of fluid and solid mechanics, porous medium transport, soft matters, scaling laws, and applications related to energy conversion. At the micro and nano scales, realization of many technologically viable ideas relies on the skillful integration of mechanics at macroscopic and molecular levels, both for solids as well as fluids. Research in the related areas is no longer confined to the understanding of the governing the physics of the system, but is also responsible for triggering a technological revolution at small scales. This book also:     Discusses the fundamentals of mechanics over micro and nano scales in a level accessible to multi-disciplinary researchers, with a balance of mathematical details and physical principles     Covers mechanics of soft matters and instabilities of thin films over small scales in a lucid manner     Delineates the mechanics of porous medium transport through an integrated approach     Demonstrates the explicit interconnection between various scale issues and the mechanics of miniaturized systems     Examplifies a mechanistic viewpoint of meso-scale energy conversion systems     Mechanics Over Micro and Nano Scales is an ideal book for researchers and engineers working in mechanics of both solids and fluids.